Activation of wild-type p53 by MDM2 inhibitors: a new strategy for lymphoma treatment - Pujals A (Dove Medical Press, 2015)
Anaïs Pujals,1–3,* Loëtitia Favre,4,* Philippe Gaulard,1–3 Joëlle Wiels41Department of Pathology, Assistance Publique-Hôpitaux de Paris, CHU Henri Mondor, 2Faculté de Médecine, Université Paris-Est Créteil, 3Inserm U955, Institut Mondor de Recherche Biomédicale, 4UMR 8126 CNRS, Institut Gustave Roussy, Université Paris-Sud, Villejuif, France*These authors contributed equally to this workAbstract: The tumor suppressor TP53 is frequently mutated or inactivated in human cancers. Mutations of TP53 are less common in lymphomas than in other tumors, but the protein is often inhibited by the overexpression of its main regulator – MDM2. In the past 10 years, major efforts have been made to develop drugs that can reactivate p53 and restore its functions. This review focuses on recent advances in the development of small inhibitors of MDM2, which are potentially relevant for the treatment of B- and T-cell lymphomas. We will describe the current state of development of these drugs and discuss their mechanism of action in these hematological malignancies.Keywords: lymphoma, p53, nutlin, apoptosis, MDM2